A careob-like nanofibers with a sustained drug release profile for promoting skin wound repair and inhibiting hypertrophic scar. (1st May 2022) - Zhang, Hongmei; Guo, Min; Zhu, Tonghe; Xiong, Hao; Zhu, Li-Min
Abstract: Excessive or disordered wound repair results in abnormal hyperplasia of scars, which intensifies the complexity and difficulty of treatment. The reported wound repair dressings, which only possess single function, can promote wound healing diminutively or treat hypertrophic scars solely. Wound healing and scar formation are the two affiliated successive stages of the wound repair process. Therefore, it is crux for the promotion of wound healing and the inhibition of scar hyperplasia synergistically. In this study, we have synthesized a 5-fluorouracil (5-Fu)-loaded dendritic mesoporous bioglass nanoparticles (dMBG) coaxial electrospun in polyethylene oxide (PEO)-poly(ether-ester-urethane)urea (PEEUU) careob-like core-shell composite nanofibers (((F@B)/P)@PU) through synergistic effect of hydrogen bonding networking and physical adsorption, and coaxial electrospinning. The 5-Fu-loaded dBMG (5-Fu@dMBG) with an optimized 5-Fu loading efficiency of 23% were shown to be successfully contained in PEO matrix, and the formed ((F@B)/P)@PU exhibited a uniform and smooth morphology, appropriate surface wettability, high protein adsorption rate, as well as matched degradation rate and mechanical properties with autologous skin tissue. Importantly, the loaded 5-Fu within ((F@B)/P)@PU exhibiteda sustained-release profile and anti-adhesion/anti-proliferation active to inhibit the growth of Hela cells, which is a model cell with the property of rapid proliferation. In addition, the wound model of rat back and H&E staining, Masson trichrome staining, CD31, CD68 and collagen I immunofluorescence staining were performed for evaluating therapeutic efficiency of ((F@B)/P)@PU. All the results revealed the better wound treatment effect of 5-Fu-loaded multistructure nanofibers for the repair of scar skin tissue defects, indicating great potential for wounds healing clinically.